DAYA TARIK DESAIN INTERIOR DAN DESAIN EKSTERIOR TERHADAP PENINGKATAN MINAT BELI KEMBALI PENGUNJUNG DI JOGJA AIRPORT RESTO - Nerys Lourensius L Tarigan; Thomas Aquinas Radito; Fajar Hardianto (Jurnal Socia Akademika, 2022)
Jogja Airport Resto is a restaurant in Jogjakarta that has a concept like a mini airport, complete with two planes along with flight attendants for demo flights in the cabin, there are x-rays, pushback control cars, luggage transport cars, checkin counters, and there are screens for flight hours. This research was conducted to test the influence of interior and exterior design on the repurchase minal of Jogja Airport Resto visitors. The results of a study involving 70 respondents showed the results that interior design had a positive and significant influence of 0.115 while exterior design had a greater positive and significant influence of 0.858. The results of the study also showed that the regression model used in this study was able to explain the influence of interior design and exterior design variables on the repurchase interest variable and was able to contribute R2 to 81.5 percent